Energy-optimal Batching Periods for Asynchronous Multistage Data Processing on Sensor Nodes: Foundations and an mPlatform Case Study - Cao, Qing; Wang, Dong; Abdelzaher, Tarek; Priyantha, Bodhi; Liu, Jie; Zhao, Feng (Proc. of IEEE Real Time Technology and Applications Symposium (RTAS2010), 2010)
This paper derives energy-optimal batching periods for asynchronous multistage data processing on sensor nodes in the sense of minimizing energy consumption while meeting end-to-end deadlines. Batching the processing of (sensor) data maximizes processor sleep periods, hence minimizing the wakeup frequency and the corresponding overhead. The algorithm is evaluated on mPlatform, a next-generation heterogeneous sensor node platform equipped with both a low-end microcontroller (MSP430) and a higher-end embedded systems processor (ARM). Experimental results show that the total energy consumption of mPlatform, when processing data flows at their optimal batching periods, is up to 35% lower than that for uniform period assignment. Moreover, processing data at the appropriate processor can use as much as 80% less energy than running the same task set on the ARM alone and 25% less energy than running the task set on the MSP430 alone.